Controlled Bistable Transmission Non-Reciprocity in a Four-Mode Optomechanical System - Jiang, Bo; Yan, Dong; Wang, Jing; Qu, Dezhan; Wu, Jin-Hui (Frontiers in Physics, 2022)
We examine the bistable transmission nonreciprocity in a four-mode optomechanical system where a mechanical oscillator interacts with one of three coupled optical cavities so as to generate an asymmetric optomechanical nonlinearity. Two transmission coefficients in opposite directions are found to exhibit nonreciprocal bistable behaviors due to this asymmetric optomechanical nonlinearity as the impedance-matching condition is broken for a not too weak input field. Such a bistable transmission nonreciprocity can be well manipulated to exhibit reversible higher isolation ratios in tunable wider ranges of the input field power or one cavity mode detuning by modulating relevant parameters like optical coupling strengths, optomechanical coupling strengths, mechanical frequencies, etc. This optomechanical system provides a flexible platform for realizing transmission nonreciprocity of weal light signals and may be extended to optical networks with more coupled cavities.